Paving the Road to Historical Novel: “Les Histoires Secrètes” in France at the Turn of the 17th and 18th Centuries - Andrey V. Golubkov (Studia Litterarum)
This article examines the genre of “secret history” which gained widespread currency in France after the publication of the book Anecdotes of Florence: or, A Secret History of the House of Medici (1685) by Antoine de Varillas. The preface to the book gives an overview of the theory of the genre that welcomes representation of hidden, sometimes “dishonorable” or “insignificant” premises of important events, usually ignored by official historiographers who tend to focus on the façade of their protagonist’s life. Authors of such “secret” stories are advised to use gossips obtained from the “royal” circles and find their way into the studies and bedrooms hidden from the eyes of the others. The article shows the impact that elements of Varillas’s poetic style (ethnographic flair, the topoi of bedroom and “cabinet,” focus on the human body etc.) had on the texts of “secret” memoirs and notes by François-Paulin Dalairac, Esaias von Pufendorf, Madeleine-Angélique de Gomez, and others. A more detailed interpretation demonstrates how historical narrative degraded into fictional prose and in many respects anticipated — together with other sources analyzed in the article — a formula of the historical novel a la Walter Scott.